HUBUNGAN ANTARA SELF-EFFICACY DENGAN KEMANDIRIAN BELAJAR PADA PESERTA DIDIK SMP DI KOTA BANDUNG - Zenica Sonia Pratiwi, - (2019)
ABSRACT Zenica Sonia Pratiwi. (2019). The Relation between Self-Efficacy and Learning Indpendence of Junior High Shool Students in Bandung (The Correlation Study of VII Grade Students at SMP Pasundan 6 Bandung in Academic Year 2018/2019). Departemen Psikologi Pendidikan dan Bimbingan, Prodi Bimbingan dan Konseling, Fakultas Ilmu Pendidikan, Universitas Pendidikan Indonesia. This research was motivated by the phenomenon of education, by forming an independent students in learning, so the students are able to face the challenges that will arise in the future. The aim of the study was to obtain a general picture of self-efficacy, a general picture of learning independence, and the relation between sef-efficacy and learning independence. This study used a quantitative approach with a correlational method. The population and sample of this study were all students of VII grade students at SMP Pasundan 6 Bandung in Academic Year 2018/2019 with respondents totaling 149 students. The data collection was obtained directly through self-efficacy inventory and learning independence inventory. The results showed a general picture of self-efficacy in the fairly confident category, and the general picture of learning independence was in the fairly independent category and there was a very strong and significant relation between self-efficacy and learning independence of VII grade students at SMP Pasundan 6 Bandung. Keyword : Self-Efficacy, Learning Independence, Relation.